Coronavirus Epidemiology, Diagnosis, and Vaccination Statistics in Pakistan, China, and India: A Brief Review - Sana Ashraf; Shakeela Parveen; Saba Ashraf; Mehwish Sultana; Urwah Ishaque; Zainab Shafqat; Saman Shabbir; Zainab Riaz; Zunaira Faiz (Current Trends in OMICS, 2024)
The global population has witnessed significant disruptions towards healthcare systems due to the Coronavirus pandemic. The World Health Organization (WHO) has designated it as a global health concern. Certain viruses within the Coronaviridae family predominantly inflict damage upon the respiratory system. The symptoms of infection may vary in severity, ranging from mild to severe, and in certain cases, can even lead to fatality. The most commonly observed symptoms include pyrexia, dyspnea, rigours, and gastrointestinal disturbances. Presently, COVID-19 stands as the prevailing subject of investigation within the academic community. The objective of the current study was to consolidate the present comprehensive material in a single source, hence enhancing the fundamental comprehension necessary for subsequent research endeavors.